Lymphoid Tissue Inducer Cells: Pivotal Cells in the Evolution of CD4 Immunity and Tolerance? - Lane, Peter J.; Gaspal, Fabrina; McConnell, Fiona; Withers, David; Anderson, Graham (Frontiers in Immunology, 2012)
Phylogeny suggests that the evolution of placentation in mammals was accompanied by substantial changes in the mammalian immune system: in particular lymph nodes and CD4 high affinity memory antibody responses co-evolved during the same period. Lymphoid tissue inducer cells (LTi) are members of an emerging family of innate lymphoid cells (ILCs) that are crucial for lymph node development, but our studies have indicated that they also play a pivotal role in the long-term maintenance of memory CD4 T cells in adult mammals through their expression of the tumor necrosis family members, OX40- and CD30-ligands. Additionally, our studies have shown that these two molecules are also key operators in CD4 effector function, as their absence obviates the need for the FoxP3-dependent regulatory T cells (Tregs) that prevent CD4 driven autoimmune responses. In this perspective article, we summarize findings from our group over the last 10 years, and focus specifically on the role of LTi in thymus. We suggest that like memory CD4 T cells, LTi also play a role in the selection and maintenance of the Tregs that under normal circumstances are absolutely required to regulate CD4 effector cells.